2020
DOI: 10.1177/1478210320922111
|View full text |Cite
|
Sign up to set email alerts
|

Privatization of early childhood education (ECE): Implications for social justice in Nepal and Kenya

Abstract: This ethnographic study examined the (un)intended 1 consequences of increased privatization of Early Childhood Education (ECE) in Nepal and Kenya. Qualitative data showed overreliance on high-stakes standardized tests increased competition for ‘good grades or examination scores’, thus (un)intentionally creating ideal conditions for proliferation of for-profit private schools that predominantly taught culturally decontextualized education at all levels of schooling. Private schools in both countries served hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…However, research has shown that a policy shift towards privatisation has also compromised equality: private ECE providers may promote educational injustice against low-income families and children (e.g. Kambutu et al, 2020; Perez and Cannella, 2011). Our interviewees did not consider what privatisation means for equality among families even though it became clear that private companies are choosing their clients and are thus excluding some children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research has shown that a policy shift towards privatisation has also compromised equality: private ECE providers may promote educational injustice against low-income families and children (e.g. Kambutu et al, 2020; Perez and Cannella, 2011). Our interviewees did not consider what privatisation means for equality among families even though it became clear that private companies are choosing their clients and are thus excluding some children.…”
Section: Discussionmentioning
confidence: 99%
“…However, ECE services are globally and increasingly understood as a business providing private commodities within a competitive market and trading these commodities to ‘consumer’ parents (see e.g. Gupta, 2018; Kambutu et al, 2020; Mahon et al, 2012; Perez and Cannella, 2011). This new understanding about ECE services is part of the neoliberal belief in market rationality (Rizvi and Lingrad, 2010), which has made ECE services subject ‘to the logic of commodification, calculation and contract’ (Dahlberg and Moss, 2005: p. 29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The curricula in Nepali fee-based, for-profit urban private preschools are based on Euro-western practices—a further indication of the influence of neocolonialism. While more local or indigenous child-rearing practices remain in rural areas and within certain castes, scholars (Kambutu et al, 2020) note that teaching in English is also favored by the government, leading to the marginalization of local languages. In Kenya, English has been adopted as the language that children use for examinations.…”
Section: Findings and Interpretationsmentioning
confidence: 99%
“…Language of instruction and the values associated with it form part of the hidden curriculum. In many postcolonial contexts, teachers continue to prioritise English as a key indicator of quality in education and English language proficiency as invaluable for future success in lieu of local languages (Kambutu et al, 2020). However, holding a colonial language as key to quality and as the official medium of instruction while Indigenous languages take the backstage reproduces and reinforces hierarchies among languages and their users.…”
Section: Introductionmentioning
confidence: 99%